Disparities in Jurisdictional Locus Between the Enforcement of Maritime Immigration and Customs Laws Based on the Provisions of UNCLOS 1982 Through an Analysis of Lawrence M. Friedman's Legal System Theory - Muhammad Choirul Yusuf; M. Alvi Syahrin; Ridwan Arifin (PDIH Untag Semarang, 2026)
Indonesia's geographical location at the intersection of two continents and oceans makes it a strategic consideration in assessing maritime development potential. To achieve maritime security resilience oriented toward the management and efficiency of maritime resources, the existence of law enforcement and legal substance in maritime zones is necessary to formulate legal certainty. The parent legal provisions governing maritime zone provisions and management rests on Law Number 17 of 1985, which ratified UNCLOS 1982, with its 320 articles and 9 annex. Among the various maritime zone provisions, there is the term